Sinking a Ship and Loading the Cannon: Interpretations of Mass Murder and The Terror - Gonzalez, Alexander (The Toro Historical Review, 2024)
This paper will work to show how government-sponsored violence for the sake of the revolution during the Reign of Terror allowed for mass murder to take place. I analyze work from people like Reynold Secher (2003), and Julie Patricia Johnson (2020) where they use locations such as the Vendee and Lyon to describe the revolutionary violence from the perspective of Anti-Revolutionaries. It tackles the historiography of studying this topic and how the field has changed over time from covering the impact on the people of these regions to its lasting effects such as the role it played in mental health as Ronen Steinburg (2015) does in her work. The works range from being published in 1983 to current-day studies of Revolutionary violence. I use the framework of mass violence to discover how the government allowed such atrocities to take place and how they influenced many events that would take inspiration from the French Revolution.